Remarks at the WBG-IMF Annual Meetings 2016 Climate Ministerial - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed briefly the history of the Paris climate agreement. Infrastructure investment expected over the next 15 years. Most of this will be in developing countries. Making sure these investments are low-carbon and climate-resilient will be important. He sees five big focus areas: 1) bake climate ambition into development planning; 2) ramp up energy efficient appliances while phasing down hydrofluorocarbons; 3) most urgently, slow down growth of coal-fired power plants; 4) make finance greener—assessing climate risks and opportunities; 5) accelerate action to reduce carbon emissions.